The Routledge Handbook of Environmental Movements (Taylor & Francis, 2022)
This handbook provides readers with up-to-date knowledge on environmental movements and activism and is a reference point for international work in the field. It offers an assessment of environmental movements in different regions of the world, macrostructural conditions and processes underlying their mobilization, the microstructural and social-psychological dimensions of environmental movements and activism, and current trends, as well as prospects for environmental movements and social change. The handbook provides critical reviews and appraisals of the current state of the art and future development of conceptual and theoretical approaches as well as empirical knowledge and understanding of environmental movements and activism. It encourages dialogue across the disciplinary barriers between social movement studies and other perspectives and reflects upon the causes and consequences of citizens' participation in environmental movements and activities. The volume brings historical studies of environmentalism, sociological analyses of the social composition of participants in and sympathizers of environmental movements, investigations by political scientists on the conditions and processes underlying environmental movements and activism, and other disciplinary inquiries together, while keeping a clear focus within social movement theory and research as the main lines of inquiry. The handbook is an essential guide and reference point not only for researchers but also for undergraduate and graduate teaching and for policymakers and activists.
English
Keywords: environmental movements,Europe,globalization,institutionalization,radicalization,Tar Wars,climate justice activism,North America,transboundary movement,United States,Canada,Latin American,social-environmental movements,violent extractivism,Asia,political liberalization,Africa,civil society,environmental activism,Arab world,Oceania,environmental conservation,anti-nuclear movements,extractivism,Indigenous,land of resisters,climate change movements,animal rights,anti-speciesism,political consumerism,food activism,environmental justice,environmental experts and expertise,environmental collective action,marketization,politics of responsibility,commercialization,environmentalism,capitalist market,social class,political values,socialization,social networks,recruitment,environmental issues,gender,Policy,legislative outcomes,public opinion and attitudes,scientific,technological,and industrial change,biographical consequences,youth,digital media,green democracy,political imaginaries,neoliberalism,inequality,EU Emission Trading Scheme,Environmental Issues,Environmental Movement Organizations,Vice Versa,Indigenous Environmental Network,Climate Justice,Hammar Chiriac,Environmental Movements,UN,Civil Society,Climate Justice Activists,Climate Movement,Contemporary Societies,Standing Rock,DAPL,Political Consumerism,Global Justice Movement,Social Reproduction,Environmental Collective Action,De Moor,Climate Action Network,NVDA,Van Stekelenburg,Nep Scale,FSC Certification; thema EDItEUR::J Society and Social Sciences::JB Society and culture: general; thema EDItEUR::J Society and Social Sciences::JP Politics and government::JPF Political ideologies and movements; thema EDItEUR::J Society and Social Sciences::JP Politics and government::JPW Political activism / Political engagement::JPWH Non-governmental organizations (NGOs); thema EDItEUR::R Earth Sciences, Geography, Environment, Planning::RG Geography; thema EDItEUR::R Earth Sciences, Geography, Environment, Planning::RG Geography::RGC Human geography; thema EDItEUR::R Earth Sciences, Geography, Environment, Planning::RN The environment::RND Environmental policy and protocols